(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The effect of aminoacids was studied on the level of protein amid groups during incubation of rat liver homogenates. It has been established that ammonia and urea formed on incubation is not due to deamination of proteins. Only some inter change was shown between readily hydrolysable and hardly hydrolysable protein amid groups.